A review of the mechanism and role of wax inhibitors in the wax deposition and precipitation - Norida, Ridzuan; Lim, Zhen Hao; Hikmat, Said Al-Salim (UPM Press, 2019)
The continuous depletion of global oil reserves with the propensity for light distillates propels the oil and gas industry to explore heavier fractions of crude oils with significant amount of paraffin waxes. However, the precipitation and deposition of waxes during the transportation of these waxy crude oils in the pipelines contribute to several issues, such as the flowability reduction, excessive pumping cost, and wax gel formation, that adversely affect the supposedly steady offshore oil production. As a result, substantial resources are expended to resolve these flow assurance problems. The wax inhibitors and pour point depressants are developed and modified to meet the wax remediation criteria. Essentially, the wax crystals are formed through the nucleation, growth, and agglomeration processes, while the deposition of these waxes occurs via molecular diffusion and shear dispersion. The wax inhibitors are able to control the growth of wax crystals through nucleation, co- crystallization, adsorption, and dispersion interactions. This paper particularly assessed the following compounds: (1) polymeric wax inhibitors, (2) nano-hybrid pour point depressants, (3) organic solvents, and (4) surfactants. Given the significance of these compounds in the deposition and precipitation of waxes, it is imperative to comprehensively explore the types and nature of these compounds and their recent applications as well as to critically assess their strengths and drawbacks, which were addressed in this paper. Furthermore, the challenges of using these compounds andthe factors that govern their efficiencies were also discussed. Accordingly, the carbon length and the molecular weight of both paraffin waxes and wax inhibitors are among the most influential factors.